(untitled) (Semiárida, 2020)
The grain yield of wheat bread and its quality show great interannual variability in the subhumid dry Pampa region. The objective this work was to evaluate the effect of genotype and nitrogen fertilization on the yield components and grain quality. The tests were carried out in the Faculty of Agronomy of the UNLPam (36° 32’ 49 "S; 64° 18’ 20" W) for 2 years and with 16 genotypes participating. The fertilized treatment was added 100 kg.ha-1 of broadcast urea in early tillering. The results showed no association between variety quality group and grain yield or protein percentage. The nitrogen fertilizer added in the tillering increased in the two years studied the percentage of protein, whereas, to the grain yield alone in the rainy year. Nor was there a clear association between the year of registration of variety in INASE and grain yield or the percentage of proteins, indicating poor genetic progress by the breeders for the subhumiddry Pampa region. We conclude that the genotype chosen, regarding quality group and registration year, is not as important as the effect of the season growth and nitrogen fertilization.